Developing and validating a scale for assessing survival ability of homegrown franchisees - Nor Hafiza, Othman; Nurul Ashykin, Abd Aziz; Nur’amirah, Mohd Yaziz; Hasif Rafidee, Hasbollah; Mohd Hizam, Hanafiah; Zuraimi, Abdul Aziz; Nurul Faizah, Halim (Malque Publishing, 2025)
Franchising is a business strategy that allow entrepreneurs to start a business using an established brand name, a proven business system, and the support of a franchisor. However, not all franchisees survive during the economic downturn and maintain profitability in their business. Therefore, recognizing the factors that impact franchisee survival is vital for sustaining and expanding the business. This study aims to develop and validate a Franchisee Survival Ability (FSA) scale among homegrown franchisees in Malaysia. A quantitative approach was utilized, with purposive sampling as the chosen technique. Out of the 120 questionnaires distributed to franchisees, only 100 were returned with completed responses. Exploratory factor analysis was employed to identify and validate the key factors influencing the survival ability among franchisee business using IBM SPSS version 26. The findings showed that the FSA scale were valid and reliable for measuring the FSA scale, namely, financial resources, brand orientation, value proposition, and government support. These factors collectively account for a total variance of 71.76% in this study. The research provides a robust instrument for assessing the franchisee's survival abilities and significantly adds to the franchising literature. It underscores government intervention's crucial role in supporting franchisees during economic challenges. Thus, the FSA scale serves as a pivotal resource for franchisees and policymakers, guiding informed decisions to foster long-term business success and regional viability. Future research should expand sample sizes to deepen insights into local franchisees' resilience strategies amid economic adversity. In conclusion, this study contributes essential insights into the dynamics of franchisee survival and strategies for sustaining franchise operations in varying economic conditions.